2020
DOI: 10.1093/mnrasl/slaa032
|View full text |Cite
|
Sign up to set email alerts
|

xGASS: passive discs do not host unexpectedly large reservoirs of cold atomic hydrogen

Abstract: We use the extended GALEX Arecibo SDSS Survey (xGASS) to quantify the relationship between atomic hydrogen (Hi) reservoir and current star formation rate (SFR) for central disk galaxies. This is primarily motivated by recent claims for the existence, in this sample, of a large population of passive disks harbouring Hi reservoirs as large as those observed in main sequence galaxies. Across the stellar mass range 10 9 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
5
11
0
Order By: Relevance
“…In contrast, truly passive spirals like the N U V -selected red spirals in our sample are expected to be gas poor, in terms of both atomic gas (e.g. Cortese 2012;Cortese et al 2020) and molecular gas (e.g. Luo et al 2020).…”
Section: Radial Gradientsmentioning
confidence: 86%
“…In contrast, truly passive spirals like the N U V -selected red spirals in our sample are expected to be gas poor, in terms of both atomic gas (e.g. Cortese 2012;Cortese et al 2020) and molecular gas (e.g. Luo et al 2020).…”
Section: Radial Gradientsmentioning
confidence: 86%
“…Recently Zhang et al (2019) claimed that even "quiescent" massive disk galaxies have an Hi content comparable to their star-forming counterparts. However, Cortese et al (2020) countered this claim by analyzing the SFRs used by Zhang et al (2019). They found that the SFRs used by Zhang et al (2019) were systematically low, thus the galaxies they considered quiescent were in fact star forming.…”
Section: The Relation Between Molecular and Atomic Gasmentioning
confidence: 99%
“…As discussed in Z19, using different SFR estimators may produce different results. Cortese et al (2020) show that utilizing the SFRs calculated from UV and IR photometry will lead to different conclusions. To address this concern, we repeat all analysis in this paper by using the SFRs derived from the SED fitting of UV, optical, and mid-IR bands (GSWLC-M2 catalog; Salim et al 2016;Salim et al 2018).…”
Section: The Effect Of Using Alternative Sfr Estimatormentioning
confidence: 97%